Digital-based Islamic Education Curriculum Innovation Rooted in Islamic Values - Indra Azwar Mawardi; Marwan Setiawan (UIN Sunan Gunung Djati Bandung, 2025)
Digital transformation presents significant challenges and opportunities in Islamic education, especially in integrating Islamic values into a digital-based curriculum. This research aims to explore the implementation of digital transformation in Islamic education, identify the challenges faced, and explore opportunities to improve the quality of Islamic value-based learning. This research used a qualitative approach through case studies of Islamic education institutions that implemented a digital curriculum. Data were collected through in-depth interviews, participatory observation, and document analysis. Thematic analysis was applied to explore the main themes related to the challenges and opportunities in the digital transformation of Islamic education. Digital transformation increases the accessibility and flexibility of Islamic education through e-learning platforms and the use of digital media. Technology helps create more engaging and interactive learning experiences, thereby increasing student motivation. However, key challenges include gaps in technology access, a lack of teacher training, and resistance to change. However, the integration of technology enables personalised learning and digital literacy of students that is relevant to the needs of the times. Digital transformation has great potential to revitalize Islamic education by improving accessibility, relevance, and student engagement. However, successful implementation requires infrastructure development, teacher training, and a curriculum rooted in Islamic values. Further research is recommended to address the challenges of the technology gap and to explore the long-term impact of this transformation on Islamic education.